Effects of internal target structures on laser-driven neutron production. (10th June 2019) - Zhang, Yihang; Wang, Wei-Min; Li, Yutong; Zhang, Zhe; McKenna, Paul; Neely, David; Zhang, Jie
Abstract: We study neutron production in interactions of an intense laser pulse with solid, near-critical density and foam targets, by two-dimensional particle-in-cell simulations. We find that compared with solid and near-critical density targets, the neutron production from foam targets is more efficient because ion acceleration and ion-ion collisions are significantly enhanced. This is caused due to formation of ambipolar electrostatic fields among the multi-lamellas in the foam. The energy conversion efficiency from the laser pulse to the ions inside the foam target is up to 11%, 12-fold higher than the one achieved with a solid target for the same laser parameters. We also find that a foam target with thinner lamellas and larger pores between the lamellas is more favorable for neutron production due to higher laser energy absorption and longer distance for ion acceleration. The number of the neutrons can reach 10 7 from a foam target with a thickness of only 20 driven by a 10 20 laser pulse.